A implantação da educação financeira no ensino fundamental. - FERREIRA, Nicole Garcia Vaz; DIAS, Priscila Tomas da Silva; MOREIRA, Yasmin Bastos Nicolau (261, 2023)
O principal foco desse trabalho foi pesquisar e analisar qual a porcentagem de conhecimentos referentes a educação financeira da população para destacar o quão importante é repassar não só dentro das residências, mas sim impregnar um ensinamento nas escolas ainda no nível fundamental onde as crianças já cresceriam com algum tipo de lucidez sobre a utilização correta do dinheiro, provando que ao utilizá-lo de forma certa e ajuizada suas vidas financeiras teriam mais sucesso. Por meio de artigos e estudos de autores como Gadotti, Freire, Gadot, Jacob e muitos outros, os quais afirmam o que já pode ser percebido; a falta da educação financeira atinge tanto a vida econômica quanto social, atingindo também a relação familiar. Contudo, é possível considerar que, com a implantação da educação financeira nas escolas as próximas gerações, por devagar que seja, podem mudar os processos políticos, socioeconômicos e até a qualidade de vida mundial. Por fim, realizamos uma pesquisa via Google Forms (formulário do google), onde enviamos perguntas para entender qual nível de conhecimento e importância que a educação financeira tem para as famílias. Palavras chave: Educação, finanças, educação fianceira, ensinamento.

ABSTRACT The main focus of this work was to researchand analyse the percentage of knowledge regarding financial education of population to highlight how importante it is to passo n not only within homes,butalso to impart teaching in schools eve at the elementar level where children would already growup with some type of licidiy about the corret use of Money,proving tha by using it corretctly and wisely theirfinancial lives would be more successful. Through articles and studis by authorssuch as Gadotti,Freire,Gadot,Jacob and many others who afim what can already be perceived; The lack of financial education affects both economic and social life,also damaging Family relationships. Howevwe,it is possible to consider that,with the implementation of financial education in schools,the next generations,howewer slowly,can change political,socioeconomic processes and even the worlds’s quality of life.Finally,we carried out a survey via Google Forms (google form),where we sent questions to undertand the level of knowledge and importance that financial education has for families. Keywords:Education,Finance,Financial Education,Teaching.

ABSTRACT This work aims to analyze the importance of studying professional ethics and its impact on contemporary society, as it plays a fundamental role in the life of the administrator, as it not only affects business decision-making, but also reputation and long-term sustainability of the company. Ethical administrators are more likely to earn the trust of stakeholders, maintain a healthy work routine for their employees and make decisions that benefit not only the organization, but society as a whole. Professional ethics involves the application of moral principles and values in the practice of a given group, ensuring the integrity, trust and responsibility of each individual. By considering the impact of their actions on stakeholders and striving for moral excellence, professionals can promote social justice, the common good, and personal development. Furthermore, the study of this topic contributes to the selfregulation of professions, protecting.
Keywords: Educação; Educação financeira; Gestão e Negócios